Predisposisi Partisipasi Masyarakat dalam Perencanaan Kampung Wisata (Studi Kasus Kampung Wisata Santan) - Sutrisno, Sutrisno (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
This study aimed to analyze predisposition (readiness), especially understanding and attitudes towards the tourist village program and to analyze community participation in the declaration and plan of participation in the program tourist village. The experiment was conducted in the village (Kampung) Santan Village Guwosari, Pajangan Bantul. Respondents are determined by the census. The results showed general cognitive understanding peoples understanding of the tourist village, the knowledge of the planning and launching of Kampung Dusun Santan as Tourism is still largely lacking (only know a little bit). This is due to the constraints of socialization and domination of the village leaders in planning the tourist village less evenly involve villagers. Once people get the socialization though still very limited, affective response was very positive and support the tourist village. They hoped that Kampung Santan be more advanced and increased economy. Public participation in the tourist village program showed improved symptoms, ranging from participation since the planning, at the time of the declaration and the time after the launching. Forms of participation can be seen from the amount of involvement of communities themselves and plan the most desirable programs. Tourism Village program were most interested in the community is the provision of infrastructure, because the program is expected to bring direct benefits to the community. It is recommended that the socialization and solidarity of citizens needs to be improved so that participation can be improved.